Overexpression of a Stress-Responsive NAC Transcription Factor Gene ONAC022 Improves Drought and Salt Tolerance in Rice - Hong, Yongbo; Zhang, Huijuan; Huang, Lei; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2016)
The NAC transcription factors play critical roles in regulating stress responses in plants. However, the functions for many of the NAC family members in rice are yet to be identified. In the present study, a novel stress-responsive rice NAC gene, ONAC022, was identified. Expression of ONAC022 was induced by drought, high salinity and abscisic acid (ABA). The ONAC022 protein was found to bind specifically to a canonical NAC recognition cis-element sequence and showed transactivation activity at its C-terminus in yeast. The ONAC022 protein was localized to nucleus when transiently expressed in Nicotiana benthamiana. Three independent transgenic rice lines with overexpression of ONAC022 were generated and used to explore the function of ONAC022 in drought and salt stress tolerance. Under drought stress condition in greenhouse, soil-grown ONAC022-overexpressing (N22oe) transgenic rice plants showed an increased drought tolerance, leading to higher survival ratios and better growth than wild type plants. When grown hydroponically in Hogland solution supplemented with 150 mM NaCl, the N22oe plants displayed an enhanced salt tolerance and accumulated less Na+ in roots and shoots as compared to the wild type plants. Under drought stress condition, the N22oe plants exhibited decreased rates of water loss and transpiration, reduced percentage of open stomata and increased contents of proline and soluble sugars. However, the N22oe lines showed increased sensitivity to exogenous ABA at seed germination and seedling growth stages but contained higher level of endogenous ABA. Expression of some ABA biosynthetic genes (OsNCEDs and OsPSY), signaling and regulatory genes (OsPP2C02, OsPP2C49, OsPP2C68, OsbZIP23, OsAP37, OsDREB2a and OsMYB2) and late stress-responsive genes (OsRAB21, OsLEA3 and OsP5CS1) was upregulated in the N22oe plants. Our data demonstrate that ONAC022 functions as a stress-responsive NAC with transcriptional activator activity and plays a positive role in drought and salt stress tolerance through modulating an ABA-mediated pathway.